Successful Management of Blue Rubber Bleb Nevus Syndrome (BRBNS) with Sirolimus - Ugochi O. Ogu; Ghada Abusin; Rolla F. Abu-Arja; Janice M. Staber (Case Reports in Pediatrics)
Blue rubber bleb nevus syndrome (BRBNS) is a rare disease with vascular malformations in several systems of the body, most commonly the skin and gastrointestinal tract. Bleeding from the gastrointestinal (GI) tract is a major complication, which may lead to chronic iron deficiency anemia and the need for frequent blood transfusions due to ongoing gastrointestinal blood loss. In this case report, we describe a now 19-year-old female with BRBNS who required six blood transfusions per year and after starting sirolimus is symptom- and transfusion-free.